PP.09.29: AORTIC DILATATION IN PATIENTS WITH PRIMARY ALDOSTERONISM AFTER THERAPY WITH MINERALOCORTICOID RECEPTORS ANTAGONISTS. (June 2015) - Catena, C.; Colussi, G.L.; Capobianco, F.; Russo, A.; Sechi, L.A.
Abstract : Objective: To evaluate aortic disease in patients with primary aldosteronism (PA) treated with spironolactone in comparison with PA patients treated with surrenectomy. Design and method: In 22 patients with idiopathic PA treated with spironolactone or canrenoate we evaluate aortic root (AR) and ascending aorta (AA) diameter, indexed for body surface area, LV mass indexed (LVMI) and plasma aldosterone levels. These patients were compared to 23 patients with PA due to adrenal adenoma after surgical treatment, matched for age, BMI, time after beginning of treatment and use of other anti-hypertensive drug classes. Results: PA patients treated with spironolactone had a greater AR dimension (16.7 ± 1.8 vs 15.6 ± 1.8 mm/m2, P = 0.025) and a higher prevalence of AR dilatation (64% vs 26%, P = 0.025) than patients surgically treated. Moreover, PA patients in spironolactone had a greater AA diameter (19.3 ± 2.3 vs 16.9 ± 2.4 mm/m2, P = 0.003) and higher prevalence of AA dilatation (45% vs 17%, P = 0.037) than PA patients surgically treated. Furthermore, patients treated with spironolactone had a slightly higher plasma aldosterone levels (183 ± 116 vs 108 ± 88 pg/mL, P = 0.059) than the control group. At multivariate analysis including age and LVMI as potential confounders, AR and AA diameters were independently associated with use of spironolactone (B = 0.266, P = 0.039 and B = 0.392, P = 0.002, respectively), but these associations lost independence including also plasma aldosterone levels into the analysis. Conclusions: In patients with PA treatment with mineralocorticoid receptors antagonists is associated with a more evident aortic disease than in patients surgically treated. This association could be mediated by non-genomic effects of MRA on arterial wall.